Perception of the attitudinal function of intonation in responding to Yes/No questions: A study of non-native English language teachers - Noor Alhusna Madzlan; Che Ton binti Mahmud (Universitas Syiah Kuala, 2018)
This study highlights the importance of intonation and its function for intelligibility in communication, particularly amongst teachers in ESL classrooms. It was carried out to ascertain non-native English language teachers' awareness of the attitudinal functions that intonation carries in responding to yes/no questions. Thirty Malay English language teachers working in a language centre were taken as the sample. Two different tasks, a listening test and an open-ended questionnaire, were provided to test their knowledge and perception of the attitudinal functions of intonation with regards to the responses given to yes/no questions. The findings from this study suggest that these teachers demonstrated an intermediate level of knowledge about intonation and its attitudinal function. However, they were in agreement about the importance of intonation for communication in classrooms, with students from various cultural and linguistic backgrounds. The implication of this study is that teachers should provide students with sufficient exposure to the proper use of intonation in order to avoid miscommunication. Students must be made aware that correct intonation facilitates correct interpretations.